DEVELOPMENT OF FINITE DIFFERENCE METHOD APPLIED TO CONSOLIDATION ANALYSIS OF EMBANKMENTS - Vipman Tandjiria (Civil Engineering Dimension, 1999)
This study presents the development of the finite difference method applied to consolidation analysis of embankments. To analyse the consolidation of the embankment as real as possible, the finite difference method in two dimensional directions was performed. Existing soils under embankments have varying stresses due to stress history and geological background. Therefore, Skempton’s parameter “A” which is a function of vertical stresses was taken into account in this study. Two case studies were chosen to verify the proposed method. It is found out that results obtained from the proposed method agree with either recorded data or results solved using another solution.